2017
DOI: 10.1007/s00436-016-5366-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo efficacy of a biotherapic and eugenol formulation against Rhipicephalus microplus

Abstract: The control of Rhipicephalus microplus is essential to prevent cattle discomfort and economic losses. However, increased resistance and acaricides inefficiency lead producers to adopt strategies that could result in the accumulation of chemical residues in meat and milk with possibilities of poisoning in animals and people. This scenario demonstrates the necessity of research into the identification of novel, effective and environmentally safe therapeutic options for cattle tick control. The objectives of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, Figueiredo et al (2018) using a 30CH biotherapeutic did not find significant differences in infestation in relation to the control group. Valente et al (2017) also reported very low effectiveness (42%) of a 6CH biotherapeutic formulation.…”
Section: Arqmentioning
confidence: 99%
“…However, Figueiredo et al (2018) using a 30CH biotherapeutic did not find significant differences in infestation in relation to the control group. Valente et al (2017) also reported very low effectiveness (42%) of a 6CH biotherapeutic formulation.…”
Section: Arqmentioning
confidence: 99%
“…Recent studies have focused on natural substances, such as secondary plant metabolites with acaricidal or repellent activities, to protect livestock against ticks (Lunguinho et al 2021 ). Notably, essential oils derived from clove, cottonseed, and lemon grass have been investigated as potential substitutes for synthetic pesticides (Valente et al 2017 ; Jain et al 2020 ; Apel et al 2009 ; Castro et al 2018 ; Santos and Vogel 2012 ). However, few studies have evaluated ethanol extracts as potential acaricides and repellents against ticks.…”
Section: Introductionmentioning
confidence: 99%
“…The tickis known as the indigenous tick to the African continent and is widely distributed in tropical and subtropical regions. Rhipicephalus decoloratus is regarded as the major vector for transmission of tick-borne diseases, such as Babesia bigemina , Anaplasma marginale , and Anaplasma central , to cattle, whereas its counteracting species, Rhipicephalus microplus , can also transmit Babesia bovis , amongst other pathogens [ 2 – 4 ]. Heavy infestation of ticks results in the production and economic losses by reducing milk yield in cows, meat, and damage to the skin.…”
Section: Introductionmentioning
confidence: 99%